Differentiation of Strategies Reflected by The Political Metaphor Use in Global Climate Negotiation: Comparison Between European Union and China - Qu, Zihuan (Transactions on Economics, Business and Management Research, 2024)
The positive attitude for global governance will be required in order to successfully address global climate change. Currently there are several examples in global climate negotiation, especially in COP 26, reflected the discordance among strategies of different international entities. In international negotiation, the specific political words that delegates used is efficient for clarifying the strategies, which are called political metaphors. In this study we are looking for metaphors by analyzing the documents from EU and China in UNFCCC. This study explored the domestic and international strategies of China and EU in international climate negotiation, which reflected by the political metaphor. The researcher first collect the documents of EU and China in website of UNFCCC. Meanwhile, we use the corpus tool, Wmatrix, which created by Lancaster University. The tendency of strategy is evaluated by the data we collected and the analysis about the metaphors. Our result show that although EU and China are both in positive attitude about dealing with climate change, they have difference in details. EU tends to formulate the rigid structure under the Paris Agreement. They concentrate on the immediate and most effective measures. By the contrast, China focuses on long-term action by using relevant metaphors. They are trying to establish the new and more sustainable structure, which will be more friendly with countries have high emission and high development requirement at the same time